Towards Tianeptine Analogues: Synthesis of New Ring Systems Containing a Dibenzo[c,f][1,2]thiazepine S,S-Dioxide Core - Berecz, Gábor; Dancsó, András; Németh, Dóra R.; Kiss, Loránd; Simig, Gyula; Volk, Balázs (Synthesis, 2022)
In the course of the synthesis of fused-ring analogues of the antidepressant drug tianeptine, representatives of three new heterocyclic ring systems, indolo[1,7-bc][1,2]benzothiazepines (and their 4,5-dihydro analogues), 5,6-dihydroquino[1,8-bc][1,2]benzothiazepines, and [1,2]benzothiazepino[4,3,2-jk]carbazoles, as well as their intermediates, have been prepared. The tetracyclic and pentacyclic ring systems containing either an oxo or a hydroxy functional group are suitable for introducing various side chains, including potential pharmacophores. For this latter transformation, examples are demonstrated by conversion of the hydroxy group into a chloro moiety and subsequent reaction with amines or with primary alcohols bearing a tertiary amino side chain. Two fused-ring derivatives exhibiting the side-chain characteristics of tianeptine have also been synthesized. Altogether 40 compounds are described in the present manuscript, eight of them are also characterized by single-crystal X-ray diffraction.
Keywords: sulfonamides; ester hydrolysis; ring closure; new ring systems; intramolecular Friedel–Crafts acylation; rearrangement